Eksplorasi Keterampilan Kolaboratif Peserta didik pada Materi Fotosintesis dan Pembelahan Mitosis - Natalia Rosa Keliat; Risya Pramana Situmorang; Desti Christian Cahyaningrum; Sri Kasmiyati; Elizabeth Betty Elok; Andreas Binar Aji Sukmana; Vivian Yolanda Halim; Ajeng Setya Magdalena; Vicharisti Monica Mangudis; Olive Hapsari Sekar Widiantari; Cantika Fanny Nurwahidah; Otilda Fatima Araujo (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
This activity aims to explore and improve the collaborative skills of students at SMA Kristen 1, Salatiga with class XII IPA students as participants. The data collection technique used a collaborative skills observation sheet with indicators 1) working productively; 2) being responsible; 3) respecting other students and; 4) compromising. The data analysis technique used the percentage of collaborative skills. In photosynthesis learning, students with collaborative skills in the exemplary category reached 14 people (19.4%), proficient 47 people (65.3%), basic 9 people (12.5%), and novice only 2 people (2.8%). In mitosis learning, students who had collaborative skills in the exemplary category were only 9 people (12.5%), proficient 52 people (72.2%), basic 8 people (11.1%), and novice only 3 people (4.2%). In the aspect of working productively in photosynthesis learning, the novice category reached 8 people (11.1%), while in mitosis learning the novice category was only 2 people (2.8%). In the aspect of being responsible for photosynthesis, the novice category reached 9 people (12.5%), while in mitosis learning, the novice category was only 4 people (5.6%). Furthermore, in photosynthesis learning in the aspect of flexibility and compromise, the novice category reached 8 people (11.1%), while in mitosis learning the novice category was only 7 people (9.7%). Based on these findings, it can be concluded that there has been an increase in the number of students who are increasingly skilled in collaborating with students.